Life drawing for artists : understanding figure drawing through poses, postures, and lighting - Legaspi, Chris (For Artists Ser., 2020)
"Life Drawing for Artists teaches a contemporary approach to figure drawing that includes both the familiar poses-standing, sitting, lying down-but also how to capture figures in movement and in more dynamic and engaging positions. Author Chris Legaspi is a dedicated, life-long artist and admired instructor who is known for his dynamic figurative drawings and paintings, and as a successful illustrator in the entertainment industry. Whether you are an aspiring illustrator, art student, or a professional artist looking to develop your abilities, Life Drawing for Artists shows how to build your skills by combining fundamental building blocks, such as gesture lines, shape and design, structure, value control, and edge or line control. You'll focus on different skills while working on both quick timed drawings and longer detailed drawings. The book covers important topics, such as drawing different views, understanding perspective, foreshortening strategies, and how to deal with various lighting conditions. The examples and tutorials explore virtually every pose scenario, as well as many active and dynamic movements. Breathe drama into your figures as you master the fundamentals with this fresh approach to life drawing."